Awareness, Adoption, and Status of Mobile-Based Library Services at University Libraries in Bangladesh: Viewpoints of Service Providers and Recipients - Rahman, Md. Hamidur; Yesmin, Shamima (Journal of library & information services in distance learning, 2025)
This study aims to explore the current trends of mobile-based library services in tertiary academia across Bangladesh. Using a mixed-method approach, it investigated students' (365) awareness and expectations regarding mobile library services through a survey; an interview was conducted to assess the perspectives of library professionals (52) on adopting mobile services in university libraries. Results reveal a significant awareness gap, with 35.6% of students still unaware of mobile library services. Students expressed strong expectations for mobile platforms, indicating mobile apps and mobile-friendly websites would benefit their studies. Library professionals recognized the potential of mobile services; however, they highlighted some challenges.